TSS Analysis (Total Suspended Soil) Using GEE (Google Earth Engine) Cloud Technology in Belawan Waters - Mardame Pangihutan Sinaga; Jono Barita Sianipar; Ady Frenly Simanullang; Goldberd Harmuda Duva Sinaga; Ewin Handoco S; Welmar Olfan Basten Barat (Politeknik Negeri Batam, 2022)
The TSS research using GEE Cloud Technology in Belawan Waters was carried out from January to May 2021. The analysis was carried out using the Sentinel-2 Satellite. TSS results obtained that the amount is 0,011010879-53,74369064 mg/liter. The content of TSS is spread evenly around the outskirts of Belawan Waters to the Middle of Belawan Waters and has passed the quality standard limit according to the Minister of Environment of Republic Indonesia that means the Harbour area is polluted and improper for drinking water as well as for fish cultivation.